Investigation of The Effect of Pv Panel Efficiency Parameter on Investment Payback Period - Benli, Hüseyin; Gürtürk, Mert (My University, 2021)
The importance of solar energy is increasing due to climate change and similar reasons. However, the biggest barriers to solar energy investments are the high initial investment cost and the long investment payback period. In this study, the effects of technological developments in the investment payback period are examined. It has been investigated how the increase in PV panel efficiency affects the investment payback period of solar energy systems. The annual average profit, the daily gain to be obtained according to the different PV panel efficiency values are calculated, and the effect of different PV panel efficiency values on the investment payback period of 1 MW PV power plant has been investigated. Levelized cost analysis has been used in this study. In the future, it has been found that the payback period of 1 MW PV power plants may be less than 3 years if high-efficiency PV panels take their place in the market.
Keywords: Solar energy; PV; PV efficiency